A study on students' perceptions of quality for cafeteria services in Kota Samarahan higher learning institution/ Siti Afeiza Hasim - Hasim, Siti Afeiza (Universiti Teknologi MARA Sarawak,Kampus Samarahan, 2015)
University is a place where students seeks knowledge and learn how to be socialized with everyone around them and get involved with campus activities. With their everyday routine they need food and drinks that can give them energy to do all of these activities and helps the brain to improve their knowledge and intelligence. Foods that are consume by students can help them concentrate in the class better and enhance their memories, it is all depends on the types of foods that they take whether it is healthy or not. This is where the cafeteria plays an important role in providing good food services to the students. The good quality of food services will ensure the students satisfaction. It includes the price, cleanliness, taste of the foods, the varieties of the foods and others. The students that is not satisfied with the hostel's cafeteria will prefer off-campus food service as a place to dine in. According to Chang, Norazah and Nalini(2014) the university cafeterias also need to improve and upgrade their services to maintain and attract new customers.